Depositional environments of well‐sorted detrital limestone from the Minatogawa Formation in the southern part of Okinawa Island, the Ryukyu Archipelago, Japan. (24th March 2018) - Fujita, Kazuhiko; Aruga, Kayo; Humblet, Marc; Nagai, Koichi
Abstract: Well‐sorted detrital limestone is one of the typical lithofacies of the latest interval of the Pleistocene Ryukyu Group, which is exposed in the Ryukyu Archipelago in southwestern Japan. The depositional environments of the limestone are interpreted to be extremely shallow and to include back‐reef lagoons or moats and subaerial sand dunes. However, detailed micropaleontological analyses have not been performed on this limestone. In this study, the interpretation of the depositional environments and paleo‐water depths was improved by quantitative examination of foraminiferal assemblages for the well‐sorted detrital limestone of the Minatogawa Formation in the southern part of Okinawa Island. Thin sections of limestone collected from the Minatogawa (Horikawa) quarry were subjected to sedimentological and foraminiferal analyses. Comparison with modern foraminiferal distribution within the Ryukyu Archipelago indicates that back‐reef and fore‐reef dwelling foraminifers characterize the fossil assemblages from the well‐sorted detrital limestone (bioclastic grainstone). Three ratios of indicator foraminiferal taxa (ratios of back‐reef to fore‐reef taxa, planktonic foraminifers to Amphistegina lobifera and Amphistegina lessonii, and Calcarina gaudichaudii to other Calcarina species), as well as multivariate analyses suggest that the well‐sorted detrital limestone was deposited in fore‐reef setting shallower than 40 m in water depth. A comparable depth range was reconstructed from the coral assemblage in the associated coral limestone, suggesting that the Minatogawa Formation was deposited in a gently inclined ramp setting with patch reefs and/or fringing reefs. Stratigraphic changes in paleo‐water depth, together with evidence of several unconformities associated with paleosol layers suggest that there were repeated transgressions and regressions, with an amplitude up to several tens of meters, when the Minatogawa Formation was deposited. Abstract : The well‐sorted detrital limestone of the Minatogawa Formation was deposited in a fore‐reef setting shallower than 40 m in water depth. The Minatogawa Formation was deposited on a gently inclined ramp with patch reefs and/or fringing reefs. There were repeated transgressions and regressions, with an amplitude up to several tens of meters, when the Minatogawa Formation was deposited.